Response surface optimization of light conditions for organic matter accumulation in two different shapes of Arthrospira platensis - Jian-Fei, Sun; Meng-hui, Shang; Xiao-nan, Zang (Frontiers in Nutrition, 2023)
Arthrospira platensis has attracted wide attention as a cyanobacteria with high nutritional value. In this research, the response surface method was used to study the effects of light cycle, light intensity and red-blue LED conditions on the growth and organic matter accumulation in spiral shaped strain A. platensis OUC623 and linear shaped strain A. platensis OUC793. The light conditions suitable for A. platensis OUC623 were as follows: growth (light time 12.005h, light intensity 35.639μmol/m2·s, LED red: blue=6.378:1); chlorophyll a (light time 12.748h, light intensity 31.062μmol/m2·s, red: blue=6.245:1); carotenoid (light time 13.118h, light intensity 32.252μmol/m2·s, red: blue=5.794:1); polysaccharide (light time 16.000h, light intensity 31.315μmol/m2·s, blue: red=6.238:1); protein (light time 12.184h, light intensity 6.115μmol/m2·s, blue: red=7.947:1); phycocyanin (light time12.001h, light intensity 5.001μmol/m2·s, blue: red = 8.000:1). The light conditions suitable for A.platensis OUC793 were as follows: growth (light time 13.521h, light intensity 40.218μmol/m2·s, red: blue=5.984:1); chlorophyll a (light time 14.217h, light intensity 44.961μmol/m2·s, red: blue =5.935:1); carotenoid (light time 14.125h, light intensity 44.497μmol/m2·s, red: blue=6.018:1); polysaccharide (light time 15.997h, light intensity 31.853μmol/m2·s, blue: red = 6.078:1); protein (light time12.000h, light intensity 5.000μmol/m2·s, blue: red = 8.000:1); phycocyanin (light time12.013h, light intensity 5.006μmol/m2·s, blue: red = 8.000:1). Under the theoretical optimal light conditions, compared with white LED, the growth rate, chlorophyll a, carotenoid, phycocyanin, protein and polysaccharide contents in strain 623 increased by 91.67%, 114.70%, 85.05%, 563.54%, 386.14%, 201.18%, and in strain 793 increased by 75.00%, 150.94%, 113.43%, 427.09%, 1284.71%, 312.38%, respectively. The two strains showed different advantages. Growth rate, chlorophyll a, polysaccharide, protein and phycocyanin content of strain 623 were higher than those of strain 793, while carotenoid was higher in strain 793. After optimization, both strains could reach a good growth state, and the growth rate and organic matter content were close. And then a 20L photobioreactor was used to expand the culture of the two strains, validating the theoretical optimal light conditions of response surface method. This study laid the foundation for the establishment of optical conditions for organic matter accumulation in two different strains of A. platensis, which provided more options for meeting the industrialization needs of A. platensis.